How Many? Calculative Practices in the Response to the Refugee Crisis of 2015 - Svenbro, Maja (Scandinavian Journal of Public Administration, 2022)
Crises are characterised by urgency and disorder, with the ordering practices of crisis management teams constituting key features of the response. In the Swedish refugee crisis that began in autumn 2015, numbers became a key analytic tool to comprehend, monitor and communicate the flow of people arriving in the south of the country. This study draws on theory from social studies of quantification, critical accounting and governing practices. It adopts a qualitative approach and investigates calculative practices in three local crisis teams in Malmö, Sweden. These knowledge producing practices are understood as connected to processes of problematisation, with potential implications that are not always considered. Quantification, although seemingly limited to the neutral, objective application of numbers, can have important political consequences, playing a role in how scarce societal resources are distributed during and after a crisis, as well as before the next one.